THE INFLUENCE OF TASK BASED LANGUAGE TEACHING AND LEARNING MOTIVATION TOWARD WRITING ACHIEVEMENT TO THE ELEVENTH GRADE STUDENTS OF SMK N 3 PALEMBANG - Rusman Roni; Rita Inderawati; Arief Rahman Hakim (ELTE Journal (English Languange Teaching and Education), 2017)
This article was aimed to find out the significance average score and motivation between TBLT and Conventional Technique. Due the interpretation of this  study, it found that: (1) there was a significant difference in writing achievement between the student who taught by using TBLT and those are taught using conventional technique since it was  found  that the result was 0.00, (2) there was significant difference in writing achievement between the students who have high motivation by using TBLT and conventional teaching technique since the result was 0.005, (3) there was significant difference in writing achievement between the students who have low motivation by using TBLT and conventional teaching technique since the result was 0.002, (4) there was significant difference in writing achievement between the students who have low and high motivation by using TBLT since the significant was lower 0.02, and (5) there was an interaction effect of technique used and student’s motivation in improving writing achievement since the result of interaction effect was lower 0.006. Based on the result, the writer concluded that the result of this research was lower than the level of significant level (0,05), and TBLT and motivation gave the significant influence for student’s  narrative writing achievement since there was a significant improvement before and after taught TBLT technique.Keywords: TBLT Technique, Motivation, and Writing